Treatment of severe tetanus with mechanical ventilation in developing country - Rusepno Hassan; Azwir Zaenal (Indonesian Pediatric Society, 1981)
Mortality of tetanus is high, particularly in severe cases managed without the aid of mechanical ventiilation.During 1950. six cases of severe tetanus were treated in the Pediatric ICU, Dr. Ciplo Mangunkusumo General Hospital Jakarta, due to recurrent apnoeic attacks.Sodium thiopental (Pentothal) were used as sedative agent for mechanical ventilation, and as muscle relaxant.Three children survived and 3 died while an IPPV from extensive bronchopneumonia (2 cases) and septicemia due to pseudomonas infection. The other complication was vertebral fracture. None of the hemodynamic and respiratory variables was caused by sodium thiopental.There were no direct complications of mechanical ventilation i.e. pneumothorax and pneumomediastinum.